Xenoline-polarized macrophages as an alternative in vitro model of tumor-associated macrophages in glioblastoma - Hasan Alrefai; Benjamin Lin; Amr Elkholy; Manoj Kumar; Taylor L. Schanel; Kevin J. Lee; Patricia H. Hicks; Joshua C. Anderson; Gao Guo; Eun-Young Erin Ahn; C. Ryan Miller; Christopher D. Willey (Acta Neuropathologica Communications)
Abstract Tumor-associated macrophages (TAMs) are the most abundant non-cancerous cell type in glioblastoma (GBM) and heavily influence GBM biology, contributing to tumor progression, therapeutic resistance, immune evasion, and neovascularization. Current in vitro models that utilize IL-4/IL-13 stimulation fail to capture the transcriptional and functional heterogeneity of TAMs observed in vivo. In this study, we utilize a serum-free indirect co-culture model with patient-derived xenolines to polarize primary human macrophages and characterize their molecular and functional phenotypes. We demonstrate that xenoline-polarized macrophages diverge from classical M1/M2 states and instead adopt transcriptional signatures reflective of TAM subsets identified from patients. Notably, macrophages polarized with the radiation-therapy selected xenoline, JX14P-RT, exhibited gene expression patterns enriched for interferon response and hypoxia, mirroring recurrent GBM samples. In contrast, JX14P TAMs showed enrichment in phagocytic gene sets. Functional validation of these phenotypes revealed discrepancies between the transcriptionally predicted and observed phenotypes, emphasizing the importance of integrating phenotypic validation in sequencing studies. Altogether, our findings establish xenoline-polarized macrophages as a useful alternative to traditional models that can be used to study immune-interactions in vitro.